Detection of Embryonic Suspensor Cell Death by Whole-Mount TUNEL Assay in Tobacco - Ce Shi; Pan Luo; Peng Zhao; Meng-Xiang Sun (Plants, 2020)
Embryonic suspensor in angiosperms is a short-lived structure that connects the embryo to surrounding maternal tissues, which is necessary for early embryogenesis. Timely degeneration via programed cell death is the most distinct feature of the suspensor during embryogenesis. Therefore, the molecular mechanism regulating suspensor cell death is worth in-depth study for embryonic development. However, this process can hardly be detected using conventional methods since early embryos are deeply embedded in the seed coats and inaccessible through traditional tissue section. Hence, it is necessary to develop a reliable protocol for terminal deoxynucleotidyl transferase (TdT) dUTP Nick-End Labeling (TUNEL) analysis using limited living early embryos. Here, we provide a detailed protocol for the whole-mount detection of suspensor cell death using a TUNEL system in tobacco. This method is especially useful for the direct and rapid detection of the spatial-temporal characters of programed cell death during embryogenesis, as well as for the diminishment of the artifacts during material treatment by traditional methods.